Adaptive time-varying formation tracking control of unmanned aerial vehicles with quantized input. (February 2019) - Wang, Yuan; He, Lei; Huang, Changqiang
Abstract: This paper considers the adaptive time-varying formation tracking control of unmanned aerial vehicles (UAVs) with quantized input. Uncertainties and nonholonomic constraint are involved in the UAV model. With a novel transformation of the final control signal, a very coarse quantization can be achieved. Adaptive quantized controllers are proposed by employing backstepping technique. It is proved that, with our proposed strategy, all signals of the closed-loop system are globally uniformly bounded, and the formation tracking error converges to an arbitrarily small residual set. Simulation results are given to illustrate the effectiveness of the proposed strategy. Highlights: An adaptive formation tracking control scheme for a group of UAVs with quantized input is presented. Uncertainties and nonholonomic constraint are involved in the UAV model. A novel transformation of final control signals can reduce communication rate of control information. All UAVs can track the reference while forming prescribed time-varying formations.